2010
DOI: 10.1089/acm.2008.0573
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Effect of Ayurvedic Formulations in the Treatment of Nutritional Anemia in Adolescent Students

Abstract: We conclude that a daily dose of Sootshekhar Rasa (250 mg) plus Sitopaladi Churna (400 mg) can produce sustainable improvement of nutritional anemia in adolescent students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…These drugs increase the agni (metabolic process) and which in turn help in correcting the deficits in the metabolism. Another study[33] has also shown the therapeutic effect and sustainability effect of Ayurveda formulations in nutritional deficiency anaemia in children.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs increase the agni (metabolic process) and which in turn help in correcting the deficits in the metabolism. Another study[33] has also shown the therapeutic effect and sustainability effect of Ayurveda formulations in nutritional deficiency anaemia in children.…”
Section: Discussionmentioning
confidence: 99%
“…Los terapéuticos empleados para tratar la anemia incluyeron formulaciones tradicionales japonesa, china y ayurvédica; la Espirulina (alga filamentosa); una dieta rica en hígado y músculo, y el extracto de lechuga. El número de sujetos incluidos en el estudio varió de 1 a 1646 participantes, con respecto al sexo, dos estudios se realizaron sobre población femenina (Akase et al (19) y Baumslag et al (20) ), tres en participantes de ambos sexos (Prakash et al (21) , Selmi et al (18) y Afolabi et al (17) ), mientras que el estudio experimental y el de serie de casos no indicaron el sexo de los participantes.…”
Section: Características De Los Estudiosunclassified
“…Solo en el caso del estudio Afolabi et al (17) , el diseño y estrategia del estudio fue diferente al resto de los estudios, pues la unidad de análisis fue la célula sanguínea falciforme humana. Los ECA y el estudio experimental consideraron como controles del estudio fármacos como la ferromia (Akase et al (17) y el almidón (Prakash et al (21) ). Los estudios cuasiexperimentales, el reporte y la serie de casos, emplearon como controles el perfil de diagnóstico y características de línea base sobre el mismo grupo de estudio.…”
Section: Características De Los Estudiosunclassified
See 1 more Smart Citation
“…One of the reasons for this may be the fact that Rasa Shastra is well tested science; hence, there was no need of fresh proof. However, few properly conducted clinical studies indicated that nutritional anemia in nonpregnant adolescent girls can be improved by a daily dose of Sootshekhar Rasa (250 mg) plus Sitopaladi Churna (400 mg) [11]. Another clinical study of Kukkutanda twak bhasma reveals statistically significant improvement in Swetapradara, an important gynecological disorder [12].…”
Section: Therapeutic Use Of Bhasmasmentioning
confidence: 99%